The Anti-Mattering Scale: Development, Psychometric Properties and Associations With Well-Being and Distress Measures in Adolescents and Emerging Adults. (February 2022) - Flett, Gordon L.; Nepon, Taryn; Goldberg, Joel O.; Rose, Alison L.; Atkey, Sarah K.; Zaki-Azat, Justeena
Previous work has focused on positive feelings of mattering, which pertain to the human need to feel significant. In the current article, we examine a complementary yet distinct construct involving feelings of not mattering that may arise from being marginalized and experiences that heighten a sense of being insignificant to others. We also describe the development, validation, and research applications of the Anti-Mattering Scale. The Anti-Mattering Scale (AMS) is a five-item inventory assessing feelings of not mattering to other people. Psychometric analyses of data from samples of emerging adults and adolescents confirmed that the AMS comprises one factor with high internal consistency and adequate validity. Our findings suggest that individuals who feel like they do not matter to others have a highly negative self-view, insecure attachment, and perceived deficits in meeting key psychological needs. Analyses established that links between elevated AMS scores and levels of depression, social anxiety, and loneliness. Most notably, scores on this new measure predicted unique variance in key outcomes beyond the variance attributable to other predictors. Overall, these results attest to the research utility and clinical potential of the AMS as an instrument examining the tendency of certain people to experience a profound sense of not mattering to others in ways that represent a unique source of risk, social disconnection, and personal vulnerability.